The Goal Orientations Scale (GOS): Validation for Portuguese students. Issue 4 (4th July 2017) - Pipa, Joana; Peixoto, Francisco; Mata, Lourdes; Monteiro, Vera; Sanches, Cristina
Abstract: Current research on achievement goals acknowledges that students can manifest different goal patterns. This study aimed to adapt and validate a self-report scale to assess the goal orientations of Portuguese students. A total of 2675 (age range 9–24 years) Portuguese students completed the Goal Orientations Scale (GOS). Through a cross-validation procedure, confirmatory factor analysis and descriptive statistics supports the existence of four different goal orientations: task, self-enhancing, self-defeating and avoidance orientations. The reliability and the internal validity estimates confirm that the GOS is an adequate instrument in assessing student goal orientations.